A brief exploration of disability as a form of diaconate. Issue 2 (15th March 2019) - Barber, Christopher
ABSTRACT: The diaconate as an ordained ministry has existed since the foundations of Christianity and evolved out of the pastoral needs of the early Christian communities. All Christians, ordained and lay are called to some form of ministry, some form of service both within their individual churches and faith communities and within the society and community in which they live and work. This paper seeks to explore a specific form of diaconal ministry and service, that of a diaconate of disability. Meanings of disability and diaconate are briefly explored along with the forms of diaconate that those with a disability can perform and the barriers to the validation of such diaconal ministry.